Development of Islamic Thought and Civilization in History Perspective - Din Muhammad Zakariya (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
The rapid development of Islamic thought throughout history, due to the open, tolerant and accommodating attitude of Muslims to the hegemony of foreign thought and civilization, love of science, academic culture, the work of Muslim scholars in government and social institutions, the development of streams that prioritize ratios and freedom of thought, increased the prosperity of Muslim countries, and the problems faced by Muslims from time to time are increasingly complex and require solutions. This type of research is library research, namely research whose main object is books or other sources of literature. That is, data are sought and found through literature review from books that are relevant to the discussion. All fields of science are subjected to study by Islamic thinkers, both religious and general sciences. The development of Islamic thought has implications for the development of Islamic civilization throughout the Islamic world. The development of Islamic thought and civilization was marked by the development of educational institutions, during the Umayyad and Abbasid dynasties and supported by other dynasties such as Andalusian Cordova, North Africa, Turkey and Islamic India. This has a significant impact on the lives of Muslims and has a strong influence on the progress of international civilization in general, from the classical period to the modern era. In this paper, we examine the supporting factors of the development of Islamic thought and civilization, the process of the development of Islamic thought and civilization throughout history, the scientific fields developed and its leaders, and the impact of the development of Islamic thought and civilization on the lives of Muslims and the international world. Keywords: Islamic Thought, Islamic Civilization, History